Pricing of Climate Risk Insurance: Regulation and Cross‐Subsidies - OH, SANGMIN S.; SEN, ISHITA; TENEKEDJIEVA, ANA‐MARIA (Journal of Finance, 2026)
ABSTRACT Homeowners insurance is central to managing the rising losses from climate‐related disasters. We show that insurance premiums are subject to starkly different regulations across states, creating persistent cross‐subsidies and price distortions. We employ states' regulatory rules in an instrumental variable estimation and a border discontinuity design to show insurers do not adjust rates in highly regulated states and compensate by raising rates in less regulated states. Rates and risks diverge in the long run, distorting cross‐state risk‐sharing and increasing insurer exits from highly regulated states. We argue these patterns stem from the interactions between rate regulation and insurers' financing constraints.